Climbing Robot for Ferromagnetic Surfaces with Dynamic Adjustment of the Adhesion System - Manuel F. Silva; Ramiro S. Barbosa; António L. C. Oliveira (Journal of Robotics)
This paper presents a climbing robot with wheeled locomotion and adhesion through permanent magnets, developed with the intention of being used in the inspection of different types of man-made ferromagnetic structures, such as towers for wind turbines, fuel storage tanks, and ship hulls. In this paper are presented the main considerations thought for its project, as well as several constructive aspects, among which are detailed its mechanical and electrical construction, the implemented control architecture, and the human-machine interface developed for the manual and automatic control of the vehicle while in operation. Although it can be manually controlled, the vehicle is designed to have a semiautonomous behavior, allowing a remote inspection process controlled by a technician, this way reducing the risks associated with the human inspection of tall structures and ATEX places. The distinguishing characteristic of this robot is its dynamic adjustment system of the permanent magnets in order to assure the machine adhesion to the surfaces, even when crossing slightly irregular and curved surfaces with a large radius.